2007
DOI: 10.17221/2230-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Lean and fat development in the whole body and hams of hybrid pigs studied by magnetic resonance tomography

Abstract: ABSTRACT:The aim of this study was to determine the influence of MHS-genotype and feeding regime on the growth and development of muscle and fatty tissue in the whole body as well as in hams of hybrid pigs. The experiment was carried out on 72 barrows that were divided into 4 groups regarding the MHS-genotype (NN and Nn) and feeding regime (standard and intensive). Data necessary to determine the volume of examined tissues were obtained by means of magnetic resonance tomography. During the fattening period the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Kusec et al (2008) pointed out the optimal slaughter weight with growth curve. Lean and fat development was analysed with magnetic resonance tomography by Margeta et al (2007).…”
mentioning
confidence: 99%
“…Kusec et al (2008) pointed out the optimal slaughter weight with growth curve. Lean and fat development was analysed with magnetic resonance tomography by Margeta et al (2007).…”
mentioning
confidence: 99%
“…The importance of studying the fatty acid composition is noted in many scientific studies [15][16][17][18]. Studies of the chemical composition and physical parameters of the pork fat are presented in table 7.…”
Section: Resultsmentioning
confidence: 99%
“…Various approaches in the studies of body composition based on repeated crosssectional MR images can be found in literature [70][71][72]. Kusec et al [73] investigated influence of MHS genotype and feeding regime by the examination of live Authors found that the intensive feeding regime did not improve muscle growth of hybrid pigs and that the more cost-effective restrictive feeding can be considered as more appropriate in pig fattening.…”
Section: In Vivo Assessment Of Pig's Growthmentioning
confidence: 99%